Development of Monolid Eye Corrective Facial Makeup E-Module - Permataputri, Feira Yasinta; Arum, Aniesa Puspa; Hidayah, Nurul (Journal of English Language and Education, 2025)
The development of the Monolid Eye Corrective Makeup E-Modul using Canva, which allows design creation and website link to export. The aim is to produce an E-Module that is feasible and practical for the Face Makeup Class. This Research and Development (RD) study uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Data were collected using questionnaires for validation by material and media experts and practicality tests by students. Data were analyzed using percentage-based categories. Validation by media experts reached 94.4% and by material experts 98.67%, both categorized as very valid. The one-to-one practicality test scored 88.79%, and the small group test scored 91.81%, both in the very practical category. Based on these results, the Monolid Eye Corrective Makeup E-Modul is considered highly feasible and practical as a learning media